Tingkat Keberhasilan Perawatan Ortodontik Crowding Anterior dengan Rotasi yang Menggunakan Alat Removable Kombinasi Sederhana - Belly Yordan (Denta Journal Kedokteran Gigi, 2016)
Background: Orthodontic treatment can be done by using the fix and removable orthodontic appliance including myofungtional. Successful treatment depends on the patient’s age, the type of malocclusion, treatment of space discrepancy, patient’s oral hygiene, operator skillsand patient cooperation. Purpose: This case report was aimed to show the success of orthodontic treatment in patient. Case: Skeletal relationship of class I with anterior crowding, class I angle dental malocclusion with anterior crowding and rotation by using a removable appliance with modification. Case management: Removable appliance used is standard with removable plate components such as passive clasp (adam’s hook claps) accompanied with some active clasps (labial bow, some springs, etc.). Button is used a additional combinationsto correct tooth positions of rotation. Conclution: The results obtained by the success of treatments which is shown in pre and post treatment photos, the overjet was reduced, the arch form became normal, the tooth malposition became normal and rotation was corrected.Facial profile appearance of the patient is getting better and the dental arrangement also became better. This proves the success rate of removable patient treatment is quite high as long as it is balanced with satisfy retention phases.